SOME SULFIDE-SILICATE ASSEMBLAGES FROM THE SAR CHESHMEH PORPHYRY COPPER DEPOSIT, KERMAN, IRAN (Journal of Sciences, Islamic Republic of Iran)
Studies of three selected sulfide-silicate assemblages from ore samples from the Sar Cheshmeh porphyry copper deposit led to some ore genetic conclusions. The presence of chalcopyrite blebs in the groundmass orthoclase and quartz from the stock suggests liquid immiscibility in a cooling late-magmatic melt. This is in favor of the orthomagmatic model proposed for porphyry copper deposits. The presence of bornite grains suggests a partly derivation of copper from biotite. This further supports the results obtained from the electron microprobe studies of the textural varieties of biotite. The presence of pyrite in the sericitized parts of biotite grains suggests a hydrothermal origin for the sericitized biotite enclosed pyrite grains.